(untitled) (Ciudades, 2017)
In this paper, I analyze the process of segregation and peripheralization that the hydroelectric dam Yacyretá generated by the relocalitión programs of many neighborhoods located on shore of the mighty Paraná River, the city of Posadas, Argentina. The peripheral location of large apartment complexes to rehouse the displace population has not only increased the process of urban segregation, but it has generated profund changes in lifestyle. The lack of employment, isolation, poverty, and lack of services and infrastructure are problems that emerge in these new places to live, as a manifestation of deprivation of urban space. Context in which they arise also various government programs for rehabilitation.